Análise das fricativas em posição de coda nas Cantigas de Santa Maria - Gementi, Mariana Moretto [UNESP] (2010)
The present study has as main objectives the mapping and the analysis of fricatives in coda position in Galician-Portuguese religious songs of Alfonso X, the Wise King. The consonant system of BP, specifically with respect to fricatives, will be considered as object of study. The initial approach of the data, to establish whether there is opposition between the sounds represented by the focused graphemes, will be taken from the structuralism model (CAGLIARI, 2002). Thus, the elucidation of some characteristics of Portuguese linguistic background may contribute to clarify facts of its current structure